2008
DOI: 10.1021/pr8000173
|View full text |Cite
|
Sign up to set email alerts
|

Site-Specific Phosphorylation Profiling of Arabidopsis Proteins by Mass Spectrometry and Peptide Chip Analysis

Abstract: An estimated one-third of all proteins in higher eukaryotes are regulated by phosphorylation by protein kinases (PKs). Although plant genomes encode more than 1000 PKs, the substrates of only a small fraction of these kinases are known. By mass spectrometry of peptides from cytoplasmic- and nuclear-enriched fractions, we determined 303 in vivo phosphorylation sites in Arabidopsis proteins. Among 21 different PKs, 12 were phosphorylated in their activation loops, suggesting that they were in their active state.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
128
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(135 citation statements)
references
References 81 publications
6
128
1
Order By: Relevance
“…However, phosphoproteomics data did also not hint at phosphorylated P-loops of any of the CDKBs (de la Fuente van Bentem et al, 2008;Sugiyama et al, 2008). Thus, we propose here that WEE1 is not a core cell cycle regulator but rather functions as a checkpoint kinase similar to the role of the Mik1 + kinase in S. pombe but targeting other substrates than a PSTAIRE CDK in Arabidopsis (Lundgren et al, 1991;Lee et al, 1994).…”
Section: The Role Of Wee1 In the Plant Cell Cyclementioning
confidence: 64%
See 1 more Smart Citation
“…However, phosphoproteomics data did also not hint at phosphorylated P-loops of any of the CDKBs (de la Fuente van Bentem et al, 2008;Sugiyama et al, 2008). Thus, we propose here that WEE1 is not a core cell cycle regulator but rather functions as a checkpoint kinase similar to the role of the Mik1 + kinase in S. pombe but targeting other substrates than a PSTAIRE CDK in Arabidopsis (Lundgren et al, 1991;Lee et al, 1994).…”
Section: The Role Of Wee1 In the Plant Cell Cyclementioning
confidence: 64%
“…(D) MPF regulation by G2 phase-specific CDK inhibitors (CKI*): a stoichiometrically acting CKI can delay MPF activation instead of inhibitory phosphorylations onto CDK-cyclin complexes. et al, 2007; de la Fuente van Bentem et al, 2008;Sugiyama et al, 2008). However, these are negative data, and caution is required in interpreting the absence of specific phosphopeptides.…”
Section: The Role Of Wee1 In the Plant Cell Cyclementioning
confidence: 99%
“…Conversely, there is no evidence for redox regulation of BAM3, and the enzyme has optimum activity at less alkaline pH (Santelia et al, 2015;Monroe et al, 2014). Furthermore, large-scale site-specific phosphorylation profiling of Arabidopsis proteins revealed the presence of one or more phosphorylation sites on both BAM1 and AMY3 proteins (de la Fuente van Bentem et al, 2008;Reiland et al, 2009;Xue et al, 2013;Heazlewood et al, 2008). Given the rapid activation of leaf starch degradation in response to the osmotic stress, it is likely that posttranslational modifications such as protein phosphorylation or redox regulation played a major role in activating BAM1 and AMY3 in the light.…”
Section: Differential Regulation and Isoform Subfunctionalization Defmentioning
confidence: 99%
“…In agreement with the concept that reversible protein phosphorylation is central to the regulation of most aspects of cell function (Johnson , 2009 ), many disordered regions present in proteins are indeed regulated by phosphorylation (Dyson and Wright , 2005 ). Phosphoproteomic profiling of A. thaliana proteins from several independent studies revealed that the A-domain as well as the full-length Toc159 is phosphorylated (de la Fuente van Bentem et al , 2008 ;Reiland et al , 2009 ). Similarly, cell fractionation followed by in vitro phosphospecific staining further demonstrated that fulllength Toc159 and the free A-domain were indeed both phosphoproteins (Agne et al , 2010 ).…”
Section: Construction Underway: the Ambiguous Role Of Toc159 Family Amentioning
confidence: 63%